Evaluation of the Service Quality Provided in Basketball Installations in Greece - Tsitskari, Ευστρατία; Vernadakis, Νικόλαος; Tzetzis, Γιώργος; Aggeloussis, Νικόλαος; Costa, Γιώργος (Inquiries in Physical Education and Sport, 2008)
The aim of this study was to test a tool for the evaluation of the service quality provided in basketball stadiums. Another aim of this study was to investigate the dimensions of perceived service quality in basketball installations and to develop and standardize a scale measuring this concept based on a sample of the Greek population. Five hundred from five basketball stadiums of Northern Greece filled in the evaluation instrument created and modified so that to fit in the Greek standards. The exploratory factor analysis and reliability analysis revealed six factors which explained 67,5% of the total variance: i) “installations”, ii) “socialization”, iii) “personnel”, iv) “show time”, v) “comfort” and vi) “convenience”. The variables used for the purpose of this study seem to be appropriate for the evaluation of the service quality provided in basketball and other sport installations. The challenge of providing a high quality sport and recreation service becomes less difficult when sport managers know what their customers think of the provided service and what they feel is important to quality. From a managerial perspective, identifying the dimensions and knowing a spectator’s evaluations of a provided service indicates the direction that management should take in investing its efforts and resources to increase the probability of the customer experiencing a positive outcome from watching.